Wheelchair basketball and community reintegration of people with a spinal cord injury - Wiggill, Wilene (University of the Free State, 2016)
As part of the occupational therapists role with a patient who suffered a spinal cord injury, the therapist aims to assist the patient in returning to his and her usual life, participating in activities that he or she regards as normal within his or her life. Such activities include basic tasks that are often taken for granted, such as caring for the home, caring for oneself and family, going to work, socialising with peers and managing one’s finances. From previous experience, it has been noted that occupational therapists often do not give enough attention to addressing the community reintegration needs of patients. Limited time, resources and too little knowledge regarding communication reintegration could contribute to this. Limited findings exist regarding the role of wheelchair basketball to address community reintegration. The researcher aspires to address this gap in the knowledge, by making use of a qualitative, explorative design within the specific context of the participants. By conducting in-depth interviews with the players of the wheelchair basketball team of the Northern Areas in Port Elizabeth, the researcher aimed to describe wheelchair basketball and the community reintegration of these participants. The interviews were conducted by Mr Kegan Topper, who is experienced in the interview process. The players in the wheelchair basketball team have acquired spinal cord injuries, and were between the age of 26 and 57 years. Informed consent was obtained from participants, and the participants were reimbursed for travel expenses. Participants had the opportunity to withdraw from the study at any time, without penalty or losing benefits. The identities of the participants will remain confidential. The researcher has used the findings to make recommendations regarding the community reintegration of people with spinal cord injuries.

As deel van die arbeidsterapeut se rol met ‘n pasiënt wat aan ‘n spinaalkoordbesering ly, is die terapeut ten doel om die pasiënt by te staan om terug te keer na sy/ haar normale leefwyse en deelname aan aktiwiteite wat hy / sy as normaal binne sy of haar lewe ervaar. Sulke aktiwiteite sluit onder andere in dat die pasiënt na sy / haar huis kan omsien, vir hom / haarself en familie kan sorg, werk toe kan gaan, kan sosialiseer met vriende en na sy / haar finansiële verpligtinge kan omsien. Uit vorige ondervinding is dit opgemerk dat arbeidsterapeute dikwels nie genoeg aandag skenk aan gemeenskapsherintegrasie van pasiënte nie. Beperkte tyd, gebrek aan hulpbronne en onvoldoende kennis van gemeenskapsherintegrasie kan hiertoe bydrae. Beperkte navorsingsbevindinge is beskikbaar met betrekking tot die rol van rolstoelbasketbal ten einde gemeenskapherintegrasie aan te spreek. Die navorser het daarna gestreef om hierdie gaping aan te spreek deur gebruik te maak van ŉ kwalitatiewe, eksploratiewe studie ontwerp binne die spesifieke konteks van die deelnemers. Deur in-diepte onderhoude uit te voer met die spelers van die rolstoel basketbal span van die Noordelike voorstede in Port Elizabeth, het die navorser beoog om rolstoelbasketbal en die gemeenskapsherintegrasie van hierdie deelnemers te beskryf. Die onderhoude was gedoen word deur Mr Kegan Topper, wat as bekwaam beskou word in die onderhoudvoeringsproses. Die spelers in die rolstoel basketbal span ly aan spinaalkoordbeserings en was tussen die ouderdomme van 26 en 57 jaar. Die navorser het ingeligte toestemming van voornemende deelnemers verkry en het ook deelnemers vergoed vir reiskoste. Deelnemers mag op enige tyd van die studie onttrek het sonder straf of benadeling. Die identiteite was die delnemers sal as vertroulik beskou word. Die navorser het die bevindinge gebruik om aanbevelings aangaande gemeenskap herintegrasie van mense met spinaalkoordbeserings te maak.
Keywords: Community reintegration; Low socio-economic status; Occupational therapy; Spinal cord injury; Wheelchair basketball; Basketball players; People with disabilities; Dissertaton (M. Occupational Therapy (Occupational Therapy))--University of the Free State, 2016